KONDISI TOTAL LEUKOSIT DAN PROTEIN PLASMA IKAN KOI (Cyprinus carpio Koi) PASCA PERENDAMAN EKSTRAK GRACILARIA VERRUCOSA YANG TERINFEKSI BAKTERI Aeromonas salmonicida - Moh. Awaludin Adam; Maftuch Maftuch (Faculty of Science and Technology University Ibrahimy, 2017)
The study was conducted to determine total leucocyte and plasma protein of infected koi (Cyprinus carpio) after immersion in the extract of Gracillaria verrucosa. The experimental design of this research was Completely Randomized Design. Different doses of extract were used five treatments and three replicates. Data was analyzed by using ANOVA (one-way) there were significant different of total leucocyte. Total protein plasma at treatments of fish infected, showed protein of ben thinner. Doses immersion treatments at 19 ppm get significant effects of humoral and celluler system the infected of koi fish.